High-intensity acute noise exposure causes anxiety in female rats by inducing hippocampal neuron apoptosis - Yifei Song; Xiaoni Wang; Haoyu Zhang; Rui Ma; Yiting Kang; Xiaohui Di; Zeguo Feng; Can Ni; Fadong Zhao; Hongwei Zhuang; Jianbao Zhang (Ecotoxicology and Environmental Safety)
Background: The increasing prevalence of acute noise exposure poses a significant threat to mental health. Identifying the intensity of noise that impair health is crucial for developing effective interventions. The study aimed to determine the acute noise intensity thresholds that elicit anxiety-like behaviors and brain damage in female rats, and then to elucidate the underlying neurobiological mechanisms. Methods: Female rats were subjected to acute noise exposure at levels of 105, 115, 125, and 135 dB to determine the intensity thresholds that elicit anxiety-like behaviors and brain damage were assessed at the 3th day and 1 month post-exposure. Results: We found that acute noise exposure at 135 dB induced significant anxiety-like behaviors and hippocampal neuron apoptosis on the third day, with these effects persisting up to one month after exposure. KEGG enrichment analysis of differentially expressed genes (DEGs) revealed alterations in the PI3K-AKT signaling pathway, as confirmed by Western blot analysis. Conclusions: Our findings indicate that acute noise exposure at 135 dB elicits anxiety-like behaviors in female rats on the third day post-exposure, with these effects persisting up to one month. This sustained anxiety is attributed to the inhibition of the PI3K-AKT signaling pathway and the subsequent activation of the apoptotic Caspase-3/BCL-2/BAX pathway, culminating in hippocampal neuron apoptosis.